ENVIRONMENTAL DISCLOSURES AND EARNINGS MANAGEMENT : REVIEW AND SYNTHESIS - Sarumpaet, Susi (JURNAL BISNIS STRATEGI, 2006)
This paper discussesÂ  the theoretical concept of environmental disclosures and earnings management. Two theoriesÂ  are used in the framework, namely: fegitimacy theory and political costs theory. According to legitimacy theory, firms will disclose environmental information to their stakeholders in order to maintain legitimacy. On the other hand, political Cost theory asserts that politically visible companies (e.g. large, high profit), are vulnerable to political costs and hence will attempt to reduce the possibility of adverse political attention. In doing so, these firms may convey environmental campaigns through voluntary disclosure and, lobby the politicians by managing earnings. Previous studies have revealed consistency With the arguments above. Studies on environmental disclosures found that firms disclose environmental information to maintain legitimacy. Other studies showed that environmental disclosure is associated with size and industry sector, as the proxies for political costs. Recent investigations also found that firms engaged in earnings management in order to reduce political costs derived environmental litigations, potential environmental regulations and poor environmental performance. It is concluded that more empirical studies are needed to refine the environmentalÂ related earnings management area, whereas research methodology may be focused on the environmental disclosure area.